Cardiovascular and metabolic effects of ovarian suppression in combination with tamoxifen or an aromatase inhibitor as adjuvant therapy for early oestrogen receptor-positive breast cancer: a systematic review - Ying X. Gue; Dorothy Lau; Alena Shantsila; Gregory Y.H. Lip; Carlo Palmieri (Archives of Medical Science)
Introduction Adjuvant endocrine therapy is a key treatment in oestrogen receptor positive early breast cancer (BC). For premenopausal women, ovarian function suppression (OFS) in combination with either tamoxifen or aromatase inhibitor (AI) is utilised in high-risk cases. The resultant suppression of circulating oestradiol from OFS could have adverse cardiovascular and metabolic effects, subsequently increasing the risk of cardiovascular disease.